Perception of empowerment and therapeutic adherence in type 2 diabetes and lycemic control in patients of a primary health care unit from Tabasco, Mexico. - Rodríguez Burelo, María del Rosario; Ávalos García, María Isabel; Garrido Pérez, Silvia María Guadalupe; López-Ramón, Concepción (Horizonte Sanitario, 2019)
Objective: To analyze the perception of empowerment and therapeutic adherence in patients with Type 2 Diabetes and their glycemic control in a primary care unit in Tabasco, Mexico.Materials and methods: Observational, cross-sectional and analytical study in a sample of 100 patients with diabetes. We analyzed variables of perception of empowerment, therapeutic adherence, sociodemographic and clinical. As a dependent variable, the figure of glycosylated hemoglobin HgA1c was taken as the gold standard of metabolic control. An instrument integrated by the DES-28 scale was applied to assess perception of empowerment, a questionnaire to assess the perception of Adherence of Bayarre-Grau. For the analysis, descriptive and inferential statistics (Pearson’s X2) were used with the SPSS V22.0 software.Results: The patients with diabetes were women 72%, average of age 56 years, married 60%, housewives 68%, primary studies 43%, average BMI 30.8, average of years with diabetes 8.9, main complication diabetic neuropathy 61% , mean of HgA1 figure of 8.675%, with HgA1 figure altered 82%, patients perceived to be empowered were 86%, of these, 80.2% showed lack of control with an x2 of 1,300 and a value of p = .000, with adherence 84%, of these patients resulted with altered glycemic control 83.3% with an x2.632 and a value of p = .000.Conclusions: Patients who feel empowered and adherent to treatment in our study have inadequate glycemic control, which allows us to conclude that it is necessary to investigate other factors that go beyond perception and an area of opportunity would be to implement effective strategies to achieve results successful.Key words: Type 2 Diabetes mellitus, Self-efficacy, Therapeutic adherence, Glycosylated hemoglobin (HgA1c).